"Reshaping Economic Geography. World Development Report 2009" - Romero Rodríguez, José Juan (Revista de Fomento Social, 2009)
Recension de la obra de: WORLD BANK (2008) Reshaping Economic Geography. World Development Report 2009, Washington, World Bank, 149 pp. (1ª parte) y 261 pp. (2ª parte)